Militarizing culture : essays on the warfare state - González, Roberto J. (Roberto Jesús), 1969- (Left Coast Press, 2010)
Militarizing Culture is a rousing critique of the increasing infiltration of military culture into American society by leading cultural commentator. Despite its pervasiveness, González insists that warfare is not an inevitable part of human nature, and charts a path toward the decommissioning of culture.